Health‐related quality of life in adult‐type ovarian granulosa cell tumor survivors - Ulla‐Maija Haltia; Saku Torvinen; Saara Bryk; Harri Sintonen; Johanna Tapper (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Adult‐type granulosa cell tumor (AGCT) is a rare, slow‐growing ovarian neoplasm with a tendency for late relapses. Surgery is the cornerstone of the treatment, and chemotherapy and hormonal treatment are administered in advanced and recurrent disease. The objective of our study was to assess health‐related quality of life (HRQoL) in AGCT survivors. Material and Methods 15D and European Organization for Research and Treatment of Cancer (EORTC‐QLQ‐C30) questionnaires were collected from our prospective AGCT patient cohort, consisting of 171 AGCT survivors. The age‐standardized general female population was used as a reference for 15D comparison. Clinical and sociodemographic variables and EORTC‐QLQ‐C30 symptom and function scales were used as independent variables in regression analysis explaining the variance in the 15D score. Results Eighty‐six women (50.3%), with a mean age of 68 years, returned the questionnaires. The HRQoL of AGCT survivors was similar to the general female population. The mean 15D score in our patient group was 0.891 (reference population score 0.899, p = 0.454). The scores were slightly lower on the 15D dimensions of excretion and sexual activity, whereas mental function scores were higher compared with the reference population. A history of tumor recurrence, an increasing number of other chronic illnesses, and financial difficulties each diminished HRQoL in our patient cohort. Regressing the EORTC variables on 15D produced a high explanatory power and accurate predictions of 15D scores. Conclusions HRQoL of AGCT survivors was equal to that of the controls. Mapping EORTC‐QLQ‐C30 to 15D validly predicted 15D scores in AGCT survivors, confirming the usefulness of generic 15D for estimating quality‐adjusted life years in cancer patient trials.